2021
DOI: 10.1097/md.0000000000026503
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte blood levels that remain low can predict the death of patients with COVID-19

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been rapidly spreading on a global scale and poses a great threat to human health. However, efficient indicators for disease severity have not been fully investigated. Here, we aim to investigate whether dynamic changes of lymphocyte counts can predict the deterioration of patients with COVID-19. We collected data from 2923 patients with laboratory-confirmed COVID-19. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
7
26
0
1
Order By: Relevance
“…The study by Zhang H.J. et al [28] showed that reduced absolute counts of lymphocyte blood levels that remain low can predict the death of patients with COVID-19. Belaid B. et al [19] hypothesized that the lymphopenia is a direct consequence of the substantial cell migration to the site of infection where the immune response is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Zhang H.J. et al [28] showed that reduced absolute counts of lymphocyte blood levels that remain low can predict the death of patients with COVID-19. Belaid B. et al [19] hypothesized that the lymphopenia is a direct consequence of the substantial cell migration to the site of infection where the immune response is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses 2,4,5,16,17 and individual studies 18,19 have concluded that elevated levels of inflammatory markers are associated with severity and mortality in COVID-19 cases. This anyway is obvious because the elevated (low of ALC) levels of these markers indicate greater tissue damage that leads to deterioration of the condition of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Their report suggests that, on average, nearly 90% of severe patients had elevated LDH against only nearly 32% in non-severe patients. In a study of 923 patients in China, Zhang et al 19 concluded that ALC levels remaining low after the first week following symptoms onset are highly predictive of inhospital death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent months, the predictors of worse outcomes, such as age and the presence of severe chronic comorbidities, including cardiovascular and pulmonary diseases, were defined [ 3 , 4 , 5 , 6 ]. Biomarkers, such as neutrophile-to-lymphocyte ratio and interleukin-6, were established as independent predictors of COVID-19 worsening, although their evaluation was not possible until the blood sample was taken [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%